Clavicle fractures - epidemiology, biomechanics of injury and treatment methods - Kostecki, Bartosz; Jurek, Aleksander; Klocek, Konrad; Hajduk, Aleksandra; Mrozek, Łukasz; Zwolski, Maciej; Szumlas, Zuzanna; Puchalski, Krzysztof; Tekielak, Anna (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The aim of this study is to to review and analyze scientific research on the topic of clavicle fractures, including epidemiology and comparison of the current conservative and surgical treatment options. State of Knowledge: Due to its structure and function as a support for the upper limb, the clavicle is one of the most frequently fractured bones in the human body. Any significant force acting on the shoulder, such as direct trauma or a fall onto an outstretched hand, can result in high stress forces, leading to a clavicle fracture. Depending on the location of the fracture, muscles pull the bone fragments in their respective directions, which affects the treatment approach for each type of fracture.To facilitate the choice of treatment method, classifications such as the Neer classification and the Edinburgh classification have been developed. Various surgical techniques as well as conservative treatments have been employed in the management of clavicle fractures. Conclusions: The epidemiology of clavicle fractures shows a higher incidence in young males, particularly related to sports activities. The majority of fractures occur in the middle third of the clavicle, with fractures in the distal and proximal thirds being less common. Understanding the ligamentous connections of the clavicle is crucial for understanding fracture patterns. There is no single preferred method of treatment, therefore both conservative and surgical methods are used in the therapeutic process depending on the fracture type. The functional outcome of various surgical techniques is similar.